FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DI MALUKU UTARA - Ismail, Zulkarnain; Jacob, Jufri; Nasar, Fahima (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
This research aims to empirically test how big the influence of labor, work force and investment is on economic growth in North Maluku Province. This research uses quantitative data, namely data in the form of numbers or can be calculated, statistical analysis is more appropriate to use on this data. This method must also use computer software quantitative tools. Regression Analysis Statistical Test is a procedure used to test whether there is an error or truth in the null hypothesis results from the sample. There are 3 types of criteria in testing, including the coefficient of determination test (R2), statistical t test, and statistical f test. Based on partial research results, the labor variable has a positive but not significant effect on economic growth, the labor force variable has a positive and significant effect on growth, then the investment variable has a positive but not significant effect on economic growth in North Maluku Province. And simultaneously or simultaneously, it can be seen that the three variables of labor, labor force, and investment have an influence on economic growth in North Maluku Province